Improving the Treatment of Children with Orbital Complications - Khushvakova N. Zh.; Ulashov Sh. M. (Researchparks Publishing, 2022)
Relevance: Acute rhinosinusitis (ORS) is a common childhood disease characterized by inflammation of the nose, which usually occurs after allergic or seasonal rhinitis or most often as a result of a viral infection and can be aggravated by pathogenic bacteria. Orbital complications of ALS are relatively common in the children's age group. Orbital complications tend to progress rapidly, leading to visual disturbances, thrombophlebitis and serious intracranial complications.[1] The spread of infection into the post-perinatal space creates a significant risk of complications, such as irreversible vision loss, brain abscess, cavernous thrombosis, and negative consequences, such as prolonged hospitalization and antibacterial therapy, as well as the need for surgical intervention.[2]